Multifocal chondrosarcoma of the hand: Case report and review of the literature. Issue 6 (9th June 2021) - Jones, Hunter B.; Murphree, Jacob; Suryavanshi, Joash R.; Osemwengie, Bradley O.; Rosqvist, Sterling; Cox, Cameron T.; MacKay, Brendan J.
Abstract: Few multifocal hand chondrosarcomas have been reported. To our knowledge, this report is the first to describe multifocal hand chondrosarcoma in a patient with no evidence of prior enchondroma, Ollier's disease, or Maffucci syndrome. Abstract : Few multifocal hand chondrosarcomas have been reported. To our knowledge, this report is the first to describe multifocal hand chondrosarcoma in a patient with no evidence of prior enchondroma, Ollier's disease, or Maffucci syndrome.